EKSPLORASI ETNOMATEMATIKA PADA MAKANAN TRADISIONAL KERAK TELOR SEBAGAI MEDIA BELAJAR MATEMATIKA KURIKULUM MERDEKA - Della, Sandy Puspita; Rahmawati, Eva Yuni; Luthfiyah, Rifa Zahra; Habiba, Restu Nur; Nafisa, Sayyida (LPPM Universitas Bina Bangsa, 2024)
Ethnomathematical exploration of the traditional food kerak telor is a study that explores the relationship between mathematics and culture in a traditional culinary context. Mathematics learning includes the need for a learning approach that is contextual and relevant to local culture to increase students' interest and understanding of mathematics. The aim of this research is to reveal the mathematical patterns contained in the process of making, measuring and distributing egg crusts, as well as to understand how mathematical concepts are reflected in people's culinary practices. The method used in this research is a literature review with data collection carried out on the Google Scholar database to retrieve relevant articles. The results of the research show that the traditional egg crust food contains mathematical concepts, namely geometry, which can be used as a medium for learning mathematics in schools, especially elementary and middle schools. Thus, learning mathematics will be more meaningful because the learning sources come from their own cultural environment